Inovasi Pendidikan dalam Bidang Ketenagaan Pendidikan di Indonesia - S., Sumarni; Ismail, Fajri; Karoma, Karoma; Shania, Shania (UII Darullughah Waddawah Pasuruan, 2024)
The aim of this research is to examine educational innovation in the field of educational personnel in Indonesia today. The method used in this research is library research using various kinds of references to support the research objectives. The approach used in this literature research is qualitative, where the results of relevant statements from books, journals, articles and other secondary sources are described in the form of sentences presented in each content of the study. This research data collection used primary and secondary data sources. In analyzing the data, the author uses analytical descriptive data analysis techniques. Namely, data related to the theme being researched is collected and classified, then described and finally concluded. The results of this research show that educational innovation includes new changes, to increase abilities in achieving educational goals. It includes technology, human resources and government policy. These three things play an important role which must be collaborative, they cannot work separately, synergy is needed to build education.